Formation and Use of Open Access Resources in University Libraries during the Pandemic and Martial Law in Ukraine - SHEMAIEVA, H. V.; KOSTYRKO, T. M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2022)
Objective. The research is aimed at revealing the repository as an important tool for storing and promoting open access resources and open educational resources (OER) as a component of open access resources, and the role of the library in these processes. Methods. To achieve the purpose of the research, a complex of scientific methods was applied, including analysis and synthesis, comparison, statistical method and direct study of practical experience through the analysis of library reports. Results. During the research it was summarized the information about open access resources, in particular OER; examples of the national policy of forming repositories were considered; the experience of the formation and use of institutional repositories in the technical universities of Kharkiv and Mykolaiv was studied; the foreign experience of creating and functioning of repositories of the information-library profile was considered. Conclusions. The further direction of the university library in the promotion of the OER initiative is substantiated, namely, convergence of library activities with educational activities in the aspect of creating, planning, and organizing access to open educational electronic resources.